Novel Advances in Cognitive Impairmentin Amyotrophic Lateral Sclerosis - Shuanghui GUO, Yumei ZHANG (Zhongguo quanke yixue, 2022)
Cognitive impairment is frequently found in patients with amyotrophic lateral sclerosis (ALS) , whose presence often suggests a poor prognosis.Recent years have seen some achievements in relevant research. We reviewed the clinical features, biomarkers, genetic features and latest therapeutic progress of cognitive impairment in ALS, aiming at providing new ideas for clinical management of this disease.